The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1439-0426.2010.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and reproduction in creole perch (Percichthys trucha) in the Negro River, Argentinean Patagonia

Abstract: Age, growth and reproductive characteristics of creole perch, Percichthys trucha, were investigated in the Negro River, southern Argentina from samples collected seasonally, December 1994-December 1995 Age was estimated via scale and whole otolith reading methods. Total length (n = 413) ranged from 103 to 432 mm, and weight from 12 to 1042 g. Significant differences between the length-weight relationships of males and females were detected (P < 0.05). Isometric growth was observed in juveniles and males, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Growth parameter estimates (Ø) were similar in all studies (Table ), except for that of Patimar () and the length frequency analyses of the males in the present study, the former as result of using total length for estimation, the latter resulting in the particularly large value of the growth coefficient ( K ). The overall growth performance has minimum variance within the same species because it is independent of growth rates (Lopez Cazorla and Sidorkewic, ). The similar values confirm the accuracy of our growth estimation from otoliths.…”
Section: Discussionmentioning
confidence: 99%
“…Growth parameter estimates (Ø) were similar in all studies (Table ), except for that of Patimar () and the length frequency analyses of the males in the present study, the former as result of using total length for estimation, the latter resulting in the particularly large value of the growth coefficient ( K ). The overall growth performance has minimum variance within the same species because it is independent of growth rates (Lopez Cazorla and Sidorkewic, ). The similar values confirm the accuracy of our growth estimation from otoliths.…”
Section: Discussionmentioning
confidence: 99%
“…This cut-off length is also an intermediate value between prior reported size of maturity for P. trucha (10 and 25 cm TL; Ruiz, 1993 andLópez Cazorla andSidorkewicj, 2011, respectively). The condition of fish (K) was compared between lakes using Kruskal-Wallis (K-W) test.…”
Section: Data Analysesmentioning
confidence: 88%
“…Dei Tos et al (2010) performed a review of age and growth of freshwater fish in South America and concluded that most studies used scales to make the reading of growth rings. Currently the use of otoliths in freshwater studies have increased (Silva, Stewart 2006;Lopez Cazorla, Sidorkewicj, 2011;Lozano et al, 2014). For example, one otolith atlas of Brazilian freshwater fish with relevant information was recently published (Breem, Schulz, 2014).…”
Section: Discussionmentioning
confidence: 99%